La Base de Datos Nacional de Subvenciones y la lengua - Urrutia Libarona, Iñigo (Revista de llengua i dret, 2023)
The administrative promotion technique is one of the innovative approaches used by public authorities to foster language planning in the socioeconomic sector. Language promotion activities are somewhat complex, in terms of both competence and substance, which is analysed in this study. In addition, in recent times, the provision of subsidies has faced major challenges, especially with regard to interoperable digital platforms and digitisation, leading to significant changes in procedures and ways of operating, which has affected citizens’ language rights, as in the case of the National Subsidy Database.